When Translation Goes Wrong: Translating Idiomatic Expressions - GJurchevska Atanasovska, Katarina; Sazdovska Pigulovska, Milena (Филолошки Факултет „Блаже Конески“ - Скопје, 2017)
The aim of this paper is to illuminate specificities of literary translation focusing on translating idiomatic expressions as highly expressive parts of the lexicon with a strong connotative dimension. More specifically, the paper will outline problems which arise when idiomatic expressions are translated inappropriately and the ways in which these situations affect the translation itself. The methodology of the research includes a corpus based study of examples as well as a comparative analysis of inappropriately translated idiomatic expressions from English into Macedonian with an emphasis on the ef-fects and influences which they have on the translation and its overall stylistic dimension. Ultimately, this paper will also provide guidelines for overcoming translation problems with an educational purpose – to raise the awareness of what literary translation really means and the standards that it should meet.
Keywords: original, translation, style, connotative meaning, idiomatic expression, stylistic effect